Course book - Cotton, David (Harlow, 2005)
Contents: Critical business of our time:topics include work and leisure,travel and the web; case studies in each course book unit for real practice of key business skills
Keywords: English langauge,English langauge,Anh ngữ,Anh ngữ; Business english,Study and teaching,Tiếng Anh thương mại,Học và dạy